2012
DOI: 10.1523/jneurosci.5153-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Corticostriatal Neural System Enhances Auditory Perception through Temporal Context Processing

Abstract: The temporal context of an acoustic signal can greatly influence its perception. The present study investigated the neural correlates underlying perceptual facilitation by regular temporal contexts in humans. Participants listened to temporally regular (periodic) or temporally irregular (nonperiodic) sequences of tones while performing an intensity discrimination task. Participants performed significantly better on intensity discrimination during periodic than nonperiodic tone sequences. There was greater acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 74 publications
(89 reference statements)
6
85
1
Order By: Relevance
“…Our data seems to point to an independence between temporal preparation induced by rhythmic cues and WM at the behavioral and, presumably, at the neural level, even if previous research has pointed to overlapping brain areas (i.e., putamen and inferior frontal gyrus; Gaab et al, 2003;Geiser et al, 2012;Grahn & Brett, 2007;Griffiths et al, 1999;Protzner & McIntosh, 2007). However, any argument in that sense remains speculative since brain activity was not measured in the current study.…”
Section: Discussioncontrasting
confidence: 58%
“…Our data seems to point to an independence between temporal preparation induced by rhythmic cues and WM at the behavioral and, presumably, at the neural level, even if previous research has pointed to overlapping brain areas (i.e., putamen and inferior frontal gyrus; Gaab et al, 2003;Geiser et al, 2012;Grahn & Brett, 2007;Griffiths et al, 1999;Protzner & McIntosh, 2007). However, any argument in that sense remains speculative since brain activity was not measured in the current study.…”
Section: Discussioncontrasting
confidence: 58%
“…Nevertheless, the current null result should be taken with caution as it is based on a small sample (N ¼12). In any case, the finding that rhythmic preparation was not affected by frontal TMS in our specific experimental setting it is not surprising according to neuroimaging studies pointing to subcortical rather than cortical structures, such as the putamen (Geiser et al, 2012;Marchant and Driver, 2013), and to more posterior rather than frontal areas, such as the premotor (Schubotz et al, 2003;Schubotz and von Cramon, 2001) or parietal cortex (Bolger et al, 2014;Marchant and Driver, 2013) in the ability to anticipate events unfolding in a rhythmic structure.…”
Section: Discussionsupporting
confidence: 47%
“…Geiser et al (2012) have shown that recruitment of a cortico-striatal system facilitates auditory perceptual processing in auditory temporal cortex. Directly relevant in the context of learning speech categories, Tricomi et al (2006) observed that observed recruitment of the striatum among native Japanese adults learning of English /r/ and /l/ categories via an overt categorization task with feedback.…”
Section: Basal Ganglia Interactions With Sensory Cortexmentioning
confidence: 99%